Transition metal doped molybdenum disulfide / graphene composite material and preparation method and application thereof
By preparing transition metal doped molybdenum disulfide/graphene composite materials, the existing hydrogen evolution catalyst preparation methods are solved, and the problems of complex process, high cost and uneven doping are achieved, and efficient and simple hydrogen evolution catalyst preparation is achieved, which improves the catalytic efficiency.
Patent Information
- Application Number
- CN202411757198.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-15
AI Technical Summary
The existing hydrogen evolution catalyst preparation methods have complex processes, high costs, uneven doping, and catalytic efficiency needs to be improved.
Using a transition metal-doped molybdenum disulfide/graphene composite material, a composite material covering the graphene surface was prepared by mixing the transition metal salt and ammonium tetrathiomolybdate with a graphene oxide solution, lyophilized and heat-treated, and composite material covering the graphene surface was prepared.
The catalytic activity of the hydrogen evolution reaction is improved, the preparation process is simplified, the cost is reduced, the doping uniformity is achieved, and the possibility of large-scale production is provided.
Smart Images

Figure CN119824464A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen evolution catalysts, and particularly relates to a transition metal-doped molybdenum disulfide / graphene composite material and a preparation method and application thereof. Background Art
[0002] Hydrogen has high energy density, is environmentally friendly and pollution-free, and is considered to be the most promising clean energy carrier. Renewable energy is used to generate electricity and produce hydrogen through water electrolysis. At present, the cathode hydrogen evolution reaction of the electrolytic water hydrogen production cell mainly uses platinum catalysts. The expensive price and scarce platinum resource reserves limit the commercial promotion of water electrolysis hydrogen production technology. Therefore, the development of cheap and efficient electrocatalytic hydrogen evolution reaction catalysts is one of the current research directions.
[0003] In the hydrogen evolution reaction, molybdenum disulfide shows unique application advantages and has broad application prospects. Doping molybdenum disulfide can increase the defect sites of molybdenum disulfide, thereby further improving the hydrogen evolution reaction activity of the catalyst. However, the traditional doping method has complex processes, long reaction time, high cost, uneven doping, and the catalytic efficiency of the catalyst needs to be improved.
[0004] Therefore, it is urgent to provide a new method for preparing a hydrogen evolution catalyst, which not only simplifies the preparation process but also has high catalytic efficiency of the obtained hydrogen evolution catalyst, which is very necessary. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a transition metal doped molybdenum disulfide / graphene composite material and its preparation method and application. The transition metal doped molybdenum disulfide / graphene composite material of the present invention has high catalytic efficiency in hydrogen evolution reaction, and the preparation method of the present invention has the advantages of simple process, low cost, uniform doping, large-scale production, etc.
[0006] A first aspect of the present invention provides a transition metal-doped molybdenum disulfide / graphene composite material.
[0007] Specifically, a transition metal-doped molybdenum disulfide / graphene composite material includes graphene and transition metal-doped molybdenum disulfide nanosheets, and the transition metal-doped molybdenum disulfide nanosheets are covered on the surface of the graphene.
[0008] Preferably, the transition metal is doped into the lattice of the molybdenum disulfide nanosheets.
[0009] Preferably, in the transition metal-doped molybdenum disulfide / graphene composite material, the weight proportion of the transition metal is 0.5-2%, and more preferably 0.8-1.5%.
[0010] Preferably, in the transition metal-doped molybdenum disulfide / graphene composite material, the weight proportion of molybdenum disulfide nanosheets is 65-75%, and more preferably 68-70%.
[0011] Preferably, in the transition metal-doped molybdenum disulfide / graphene composite material, the weight proportion of graphene is 25-35%, and more preferably 30-32%.
[0012] A second aspect of the present invention provides a method for preparing a transition metal-doped molybdenum disulfide / graphene composite material.
[0013] Specifically, a method for preparing a transition metal-doped molybdenum disulfide / graphene composite material comprises the following steps:
[0014] (1) adding a transition metal salt and ammonium tetrathiomolybdate to a graphene oxide solution, mixing, and drying to obtain a precursor powder;
[0015] (2) heat treating the precursor powder obtained in step (1) to obtain the transition metal-doped molybdenum disulfide / graphene composite material.
[0016] Preferably, in step (1), the transition metal salt is selected from at least one of ferrous chloride, ferric chloride, cobalt chloride and nickel chloride.
[0017] Preferably, in step (1), the mass ratio of ammonium tetrathiomolybdate to transition metal salt is 100:(0.1-10), more preferably 100:(1-5).
[0018] Preferably, in step (1), the concentration of the graphene oxide solution is 0.1-10 mg / mL, more preferably 0.5-3 mg / mL.
[0019] Preferably, in step (1), the mass volume ratio of the ammonium tetrathiomolybdate to the graphene oxide solution is 100 mg:(20-60) mL, and more preferably 100 mg:(35-45) mL.
[0020] Preferably, in step (1), the solvent in the graphene oxide solution is water and / or tert-butanol.
[0021] Preferably, in step (2), the temperature of the heat treatment is 600-2000°C, more preferably 800-1600°C.
[0022] Preferably, in step (2), the heat treatment time is 1-30 seconds, more preferably 5-10 seconds.
[0023] Preferably, in step (2), the heat treatment process is carried out in a flash Joule heating device.
[0024] Preferably, in step (2), during the heat treatment, the heating rate is 500-2000°C / sec, for example, 1000°C / sec or 2000°C / sec.
[0025] Preferably, in step (2), the heat treatment is carried out in a protective gas atmosphere, a reducing gas atmosphere or in a vacuum.
[0026] Preferably, the protective gas is an inert atmosphere (such as nitrogen or argon), more preferably nitrogen.
[0027] Preferably, the reducing atmosphere is hydrogen or a mixture of hydrogen and argon.
[0028] Preferably, the preparation method comprises the following steps:
[0029] (1) adding a transition metal salt and ammonium tetrathiomolybdate to a graphene oxide solution, stirring the mixture evenly, and freeze-drying the mixture to obtain a precursor powder;
[0030] (2) placing the precursor powder in a flash Joule heating device for heat treatment, and cooling it to room temperature to obtain the transition metal-doped molybdenum disulfide / graphene composite material.
[0031] A third aspect of the present invention provides an application of a transition metal-doped molybdenum disulfide / graphene composite material.
[0032] The above transition metal doped molybdenum disulfide / graphene composite material is used as a catalyst in the electrocatalytic hydrogen evolution reaction.
[0033] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0034] (1) The present invention introduces a large number of heteroatom defect sites into molybdenum disulfide by means of transition metals, thereby increasing the number of catalytic active sites for the hydrogen evolution reaction of the transition metal-doped molybdenum disulfide / graphene composite material. On the other hand, the introduction of heteroatoms regulates the electronic structure of molybdenum disulfide, thereby enhancing the intrinsic catalytic activity of the molybdenum disulfide material.
[0035] (2) The composite of transition metal-doped molybdenum disulfide and graphene of the present invention can enhance the conductivity of the transition metal-doped molybdenum disulfide / graphene composite material, facilitate charge transfer during the reaction, and accelerate the reaction.
[0036] (3) The transition metal and ammonium tetrathiomolybdate in the precursor of the present invention are uniformly deposited on the surface of graphene oxide, so that the transition metal is uniformly doped in molybdenum disulfide, which is beneficial to the uniform doping of transition metal atoms.
[0037] (4) The present invention adopts the electric current Joule effect rapid heating method to prepare transition metal doped molybdenum disulfide, and the heating speed is extremely fast, and the synthesis of materials can be achieved in a short time. The preparation method is simple and convenient, the conditions are controllable, the efficiency is high, and the energy consumption cost is low.
[0038] (5) The transition metal-doped molybdenum disulfide / graphene composite material prepared by the present invention has excellent electrocatalytic hydrogen evolution reaction activity, which is much higher than that of undoped molybdenum disulfide material. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a scanning electron microscope image of the transition metal-doped molybdenum disulfide / graphene composite material of Example 1;
[0040] Figure 2 This is a scanning electron microscope image of the transition metal-doped molybdenum disulfide / graphene composite material of Example 2;
[0041] Figure 3 This is a scanning electron microscope image of the transition metal-doped molybdenum disulfide / graphene composite material of Example 3;
[0042] Figure 4 This is a scanning electron microscope image of the molybdenum disulfide / graphene material of Comparative Example 1;
[0043] Figure 5 It is a comparison chart of linear sweep voltammetry curves of transition metal-doped molybdenum disulfide / graphene composite materials of Examples 1-3, molybdenum disulfide / graphene materials of Comparative Example 1, and commercially available Pt catalyst in 1M potassium hydroxide electrolyte. DETAILED DESCRIPTION
[0044] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0045] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0046] A method for preparing a transition metal-doped molybdenum disulfide / graphene composite material comprises the following steps:
[0047] (1) adding a transition metal salt and ammonium tetrathiomolybdate to a graphene oxide solution, stirring the mixture evenly, and freeze-drying the mixture to obtain a precursor powder;
[0048] (2) placing the precursor powder in a flash Joule heating device for heat treatment, and cooling it to room temperature to obtain the transition metal-doped molybdenum disulfide / graphene composite material.
[0049] Example 1
[0050] A method for preparing a transition metal-doped molybdenum disulfide / graphene composite material comprises the following steps:
[0051] (1) adding 0.915 mg of cobalt chloride hexahydrate and 100 mg of ammonium tetrathiomolybdate to 40 ml of 1.25 mg / mL graphene oxide solution, stirring evenly, and freeze-drying to obtain a precursor powder of a cobalt-doped molybdenum disulfide / graphene composite material;
[0052] (2) The precursor powder of the cobalt-doped molybdenum disulfide / graphene composite material is placed in a flash Joule heating device under a nitrogen atmosphere for heating treatment, the temperature is raised to 1500°C within 1 second and maintained for 5 seconds and then cooled to room temperature to obtain a transition metal-doped molybdenum disulfide / graphene composite material, i.e., a cobalt-doped molybdenum disulfide / graphene composite material, denoted as Co-MoS2 / rGo.
[0053] Example 2
[0054] A method for preparing a transition metal-doped molybdenum disulfide / graphene composite material comprises the following steps:
[0055] (1) adding 0.715 mg of nickel chloride hexahydrate and 100 mg of ammonium tetrathiomolybdate to 40 ml of 1.25 mg / mL graphene oxide solution, stirring evenly, and freeze-drying to obtain a precursor powder of nickel-doped molybdenum disulfide / graphene composite material;
[0056] (2) The precursor powder of the nickel-doped molybdenum disulfide / graphene composite material is placed in a flash Joule heating device in a nitrogen atmosphere for heating treatment, the temperature is raised to 1000°C within 1 second and maintained for 10 seconds and then cooled to room temperature to obtain a transition metal-doped molybdenum disulfide / graphene composite material, i.e., a nickel-doped molybdenum disulfide / graphene composite material, denoted as Ni-MoS2 / rGo.
[0057] Example 3
[0058] A method for preparing a transition metal-doped molybdenum disulfide / graphene composite material comprises the following steps:
[0059] (1) adding 0.61 mg of cobalt chloride hexahydrate, 0.24 mg of nickel chloride hexahydrate and 100 mg of ammonium tetrathiomolybdate to 40 ml of 1.25 mg / mL graphene oxide solution, stirring evenly and freeze-drying to obtain a precursor powder of cobalt and nickel co-doped molybdenum disulfide / graphene composite material;
[0060] (2) The precursor powder of the cobalt and nickel co-doped molybdenum disulfide / graphene composite material is placed in a flash Joule heating device in a nitrogen atmosphere for heating treatment, the temperature is raised to 1200°C within 1 second and maintained for 8 seconds and then cooled to room temperature to obtain a transition metal doped molybdenum disulfide / graphene composite material, that is, a cobalt and nickel co-doped molybdenum disulfide / graphene composite material, recorded as Co2Ni-MoS2 / rGo.
[0061] Comparative Example 1
[0062] In this comparative example, no transition metal was added.
[0063] A method for preparing a molybdenum disulfide / graphene composite catalyst comprises the following steps:
[0064] (1) adding 100 mg of ammonium tetrathiomolybdate to 40 ml of 1.25 mg / mL graphene oxide solution, stirring evenly, and freeze-drying to obtain a precursor powder of a molybdenum disulfide / graphene composite material;
[0065] (2) The precursor powder of the molybdenum disulfide / graphene composite material is placed in a flash Joule heating device for heating treatment, the temperature is raised to 1200°C within 1 second and maintained for 8 seconds and then cooled to room temperature to obtain a molybdenum disulfide / graphene composite material, recorded as MoS2 / rGo.
[0066] Comparative Example 2
[0067] This comparative example is a commercially available Pt catalyst for the hydrogen evolution reaction by electrolysis of water.
[0068] Product effect testing
[0069] 1. SEM analysis of transition metal doped MoS2 / graphene composites
[0070] The transition metal doped molybdenum disulfide / graphene composite materials prepared in Examples 1, 2 and 3 and the molybdenum disulfide / graphene composite material of Comparative Example 1 were subjected to scanning electron microscopy analysis. The scanning electron microscopy results of the transition metal doped molybdenum disulfide / graphene composite material of Example 1 are as follows: Figure 1 As shown, the scanning electron microscopy results of the transition metal doped molybdenum disulfide / graphene composite material in Example 2 are as follows Figure 2 As shown, the scanning electron microscopy results of the transition metal doped molybdenum disulfide / graphene composite material in Example 3 are as follows Figure 3 As shown, the scanning electron microscopy results of the molybdenum disulfide / graphene composite material of Comparative Example 1 are as follows Figure 4 shown.
[0071] Depend on Figure 1 , Figure 2 , Figure 3 , Figure 4It can be clearly seen that obvious nanoflower-like structures are formed. The structure of the composite material nanoflowers is relatively uniform and stable, and different doping has little effect on the morphology of the nanoflowers.
[0072] 2. Hydrogen evolution performance test of catalyst:
[0073] The transition metal-doped molybdenum disulfide / graphene composite materials of Examples 1-3 and the molybdenum disulfide / graphene material of Comparative Example 1 were respectively loaded on carbon cloth as working electrodes. The loading amount of the transition metal-doped molybdenum disulfide / graphene composite materials of Examples 1-3 or the molybdenum disulfide / graphene material of Comparative Example 1 on the electrode was 0.1 mg / cm 2 , a graphite rod electrode was used as the counter electrode, and a Hg / HgO electrode was used as the reference electrode, and then the electrochemical performance was tested in 1 M (i.e., 1 mol / L) potassium hydroxide electrolyte.
[0074] The electrochemical performance test results are as follows Figure 5 As shown, Figure 5 This is a comparison of the linear sweep voltammetry curves of the transition metal doped molybdenum disulfide / graphene composite materials of Examples 1-3, the molybdenum disulfide / graphene material of Comparative Example 1, and the commercially available Pt catalyst in 1M potassium hydroxide electrolyte. Figure 5 (“Potential (V vs. RHE)” indicates the comparison between the electrode potential and the reversible hydrogen reference electrode potential, and “Current density” indicates the current density) It can be seen that: compared with Comparative Example 1, the transition metal-doped molybdenum disulfide / graphene composite materials prepared in Example 1, Example 2 and Example 3 exhibit lower overpotentials. The Co2Ni-MoS2 / rGo prepared in Example 3 with the best performance has a current density of 10 mA / cm 2 The overpotential at that time was about 115 mV, which was only 67 mV lower than the 48 mV of commercial Pt catalysts on the market. Therefore, the transition metal-doped molybdenum disulfide / graphene composite material prepared in the embodiment of the present invention has better electrocatalytic hydrogen evolution performance and has the prospect of replacing Pt catalysts.
[0075] The above electron microscope scanning and electrocatalytic hydrogen evolution performance test data show that the transition metal doped molybdenum disulfide / graphene composite material prepared by the present invention has a two-dimensional nanosheet structure and abundant active sites, and has excellent electrocatalytic hydrogen evolution performance. In addition, the method for preparing the transition metal doped molybdenum disulfide / graphene composite material of the present invention is simple, the raw material utilization rate is high, and the economic cost and time cost of preparing the catalyst can be greatly reduced.
[0076] The ammonium tetrathiomolybdate molecules used in the present invention are thermally decomposed to produce molybdenum disulfide molecules, which has the advantages of simplicity and high efficiency, so the reaction can be completed by heating for only a few seconds. Although molybdenum disulfide products can also be obtained by using sodium molybdate dihydrate and thiourea instead of ammonium tetrathiomolybdate, thiourea needs to be thermally decomposed to produce hydrogen sulfide to react with sodium molybdate dihydrate during the reaction process. Therefore, the sulfur source usually needs to be excessive, and the release of hydrogen sulfide pollutes the environment. Secondly, the reaction process of hydrogen sulfide and sodium molybdate dihydrate involves gradual diffusion in the product, and the reaction time is long, and it is difficult to complete the reaction within a few seconds. The reaction sodium source may produce sodium sulfide or sodium sulfate mixed with the product, and the product needs to be cleaned and removed impurities many times, and the process is complicated. The preparation method in the present invention only needs to uniformly mix the chloride salt of the transition metal, ammonium tetrathiomolybdate and graphene oxide and then quickly heat for a few seconds. The chlorine and ammonia in the raw materials, as well as the oxygen in the graphene oxide, can be quickly converted into gaseous state and separated from the product without the need for a complicated separation and cleaning process.
[0077] Therefore, one advantage of the present invention is that the reaction process is very rapid, only a few seconds, the product is pure and does not require secondary purification, and no toxic components such as hydrogen sulfide are produced, so the method is convenient, energy-saving and environmentally friendly. The reaction in the prior art CN107881529A takes several hours to complete, requires an excessive sulfur source, which easily produces toxic components, and the product after the reaction is mixed with impurities and needs to be further cleaned and purified, which is a cumbersome process, high energy consumption and large loss.
[0078] The best material CoS2-MoS2 / RGO in CN107881529A has a current density of 10 mA / cm 2 The overpotential is about 300mV, which is 170mV higher than the 130mV of Pt catalyst. The current density of Co2Ni-MoS2 / rGo prepared by the present invention reaches 10mA / cm 2 The overpotential at this time is about 115 mV, which is only 67 mV away from the 48 mV of the Pt catalyst. It can be seen that the material prepared by the present invention has a smaller gap with the existing commercial Pt catalyst and has greater value.
[0079] The preferred embodiments of the present invention are described in detail above, but the invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A transition metal doped molybdenum disulfide / graphene composite material, characterized in that: It comprises graphene and transition metal-doped molybdenum disulfide nanosheets, and the transition metal-doped molybdenum disulfide nanosheets are covered on the surface of the graphene.
2. The transition metal-doped molybdenum disulfide / graphene composite material according to claim 1, characterized in that: The transition metal is doped into the lattice of the molybdenum disulfide nanosheets.
3. The transition metal-doped molybdenum disulfide / graphene composite material according to claim 1, characterized in that: In the transition metal-doped molybdenum disulfide / graphene composite material, the weight proportion of the transition metal is 0.5-2%.
4. The transition metal-doped molybdenum disulfide / graphene composite material according to claim 1, characterized in that: In the transition metal-doped molybdenum disulfide / graphene composite material, the weight proportion of molybdenum disulfide nanosheets is 65-75%.
5. The transition metal-doped molybdenum disulfide / graphene composite material according to claim 1, characterized in that: In the transition metal-doped molybdenum disulfide / graphene composite material, the weight proportion of graphene is 25-35%.
6. The method for preparing the transition metal-doped molybdenum disulfide / graphene composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) adding a transition metal salt and ammonium tetrathiomolybdate to a graphene oxide solution, mixing, and drying to obtain a precursor powder; (2) heat treating the precursor powder obtained in step (1) to obtain the transition metal-doped molybdenum disulfide / graphene composite material.
7. The preparation method according to claim 6, characterized in that: In step (1), the transition metal salt is selected from at least one of ferrous chloride, ferric chloride, cobalt chloride and nickel chloride; and / or the mass ratio of the ammonium tetrathiomolybdate to the transition metal salt is 100:(0.1-10); and / or the concentration of the graphene oxide solution is 0.1-10 mg / mL; and / or the mass volume ratio of the ammonium tetrathiomolybdate to the graphene oxide solution is 100 mg:(20-60) mL.
8. The preparation method according to claim 6, characterized in that: In step (2), the temperature of the heat treatment is 600-2000° C.; and / or the time of the heat treatment is 1-30 seconds.
9. The preparation method according to claim 6, characterized in that: The heat treatment process is completed in a flash Joule heating device; and / or, during the heat treatment process, the heating rate is 500-2000°C / second; and / or, the heat treatment is carried out in a protective gas atmosphere, a reducing gas atmosphere or a vacuum.
10. Use of the transition metal-doped molybdenum disulfide / graphene composite material according to any one of claims 1 to 5 as a catalyst in an electrocatalytic hydrogen evolution reaction.
Citation Information
Patent Citations
Composite hydrogen evolution electro-catalysis material and preparation method
CN107881529A